An Introduction to Interdisciplinary Research : Theory and Practice - Keestra, Machiel; Menken, S. B. J. (Book collections on Project MUSE., 2016)
One of the major areas of emphasis in academia in recent years has been interdisciplinary research, a trend that promises new insights and innovations rooted in cross-disciplinary collaboration. This book is designed to help students understand the tools required for stepping beyond traditional disciplinary boundaries and applying knowledge and insights from multiple fields. Relentlessly focused on practical applications, the book will enable students to plan and execute their own interdisciplinary research projects.